2015
DOI: 10.1111/dpr.12100
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Use of Microfinance and Formal and Informal Credit by Farmers in Less Developed Areas of Rural China

Abstract: Based on household survey data, this article shows that farmers' demand for credit in poor areas of rural China has increased significantly in recent years, and credits from various sources are used differently in production and consumption. For example, microfinance is used primarily in livestock and non‐agricultural investments, formal credit is often used in crop production, and informal credit is largely used to meet farmers' consumption requirements. Developing a complementary system with various financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
2
16
0
3
Order By: Relevance
“…The finding is interesting. More specifically, Jia et al [79] pointed out that formal credit was mainly used for farmland production. However, this study found that formal agricultural credit did not significantly reduce farmland abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is interesting. More specifically, Jia et al [79] pointed out that formal credit was mainly used for farmland production. However, this study found that formal agricultural credit did not significantly reduce farmland abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…In China, state-owned formal financial institutions such as the Agricultural Bank of China and the Rural Credit Cooperative dominate institutional lending in rural economies. These are heavily subsidised by the government to support agricultural production [40]. Although the demand for credit is immense and has significantly increased in recent years, the use of formal finance is stagnating [34,40,41].…”
Section: Formal Credit With Collateralmentioning
confidence: 99%
“…Además, el crédito puede desempeñar un papel importante en el desarrollo del sector rural. Según Jia, Luan, Huang, y Li (2015), con el acceso al crédito los agricultores podrían asumir mayores riesgos en proyectos más rentables en lugar de invertir en proyectos de menor riesgo, pero que podrían ser ineficientes. Por lo tanto, como lo mencionan Ibrahim, Kedir y Torres (2007) entender los factores que determinan el acceso de los hogares al crédito es importante para diseñar políticas encaminadas a reducir la pobreza, especialmente en países de bajos ingresos; sin embargo, estos esfuerzos se han visto obstaculizados por la poca disponibilidad de información a nivel de hogar.…”
Section: Introductionunclassified
“…Por un lado, la regulación sobre límites a tasas de interés hace que se cree un mercado alternativo (informal) en el que las tasas de interés no están controladas. Por otro lado, diferencias en los costos de detección, monitoreo y cumplimiento de los contratos lleva a la fragmentación de los mercados de crédito.18 Véase por ejemplo Zeller (1994) para el caso de Madagascar,Mohieldin y Wright (2000) para Egipto, yJia et al (2015) para las zonas rurales de China.…”
unclassified
See 1 more Smart Citation